An overview of the risk of delay in Cyprus construction industry - Vacanas, Yiannis; Danezis, Chris (My University, 2021)
This article determines the main issues related to delay in construction projects in Cyprus. Initially, a detailed comparative review was carried out to identify the most significant causes of delay at the international level. Based on the latter and the opinions of distinguished members of the industry, a survey questionnaire was designed and distributed to a total number of 242 members of the Cyprus Scientific and Technical Chamber. The analysis of the results obtained by 54 respondents indicated particular common-practice issues that affect completion in construction projects in Cyprus, such as duration of delays, Extension of time (EOT) awards and agreements, recording methods and programmes of works. Ultimately, by using the importance of delay causes as perceived by the respondents it was determined that in Cyprus construction industry ‘variations requested by the client’ (70%), ‘mistakes and missing information from consultants’ drawings’ (55%), ‘low productivity’ (55%), ‘difficulties in financing of the works by the contractor’ (52%) and ‘inadequate programming of works’ (50%) to be the main causes of delay in Cyprus. Based on the results, specific practices are recommended for the control of delay in the completion of construction projects.
Keywords: Delay; Causes; Construction; Project management; Cyprus